Research and Modeling of Mechanical Crosstalk in Linear Arrays of Ultrasonic Transducers - CELMER, Mateusz; OPIELIŃSKI, Krzysztof J. (Archives of Acoustics, 2016)
Linear arrays of ultrasonic transducers are commonly used as ultrasonic probes in medical diagnostics for imaging the interior of a human body in vivo. The crosstalk phenomenon occurs during the operation of transducers in which electrical voltages and mechanical vibrations are transmitted to adjacent components. As a result of such additional excitation of the transducers in the array, the directivity characteristics of the aperture used changes, and consequently there is interference with proper operation of a given array and the emergence of distortions in the obtained ultrasound image that reduce its quality. This paper studies the manner of propagation of mechanical crosstalk in the designed model of a linear array of ultrasonic transducers on the basis of unwanted signals, which appeared on elementary piezoelectric transducers when power is supplied to the selected transducer in the array. The universal model of linear array of ultrasonic transducers, which has been developed, allowed the simulation of mechanical crosstalk, taking into account the cross-coupling phenomenon in all of its structure with the use of finite elements method (FEM) implemented in COMSOL Multiphysics software. The analysis of crosstalk signals showed that they consist of aggregated pulses propagating with different speeds and frequencies. This signifies the formation of different vibration modes transmitted simultaneously via different paths. The paper is an original approach which enables to identify different vibration modes and estimate their participation in the crosstalk signal and their ways of propagation. Conclusions from the research allow predicting specific design changes which are significant due to the minimization of mechanical crosstalk in linear arrays of ultrasonic transducers.